PROFESSIONAL ACTIVITIES OF A MATHEMATICS TEACHER - Ergashev, A. A.; Poʻlatova Zarifaxon Xayotxon qizi (International Journal on Integrated Education, 2023)
Methodical training of mathematics teacher in pedagogical university is a part of his/her professional preparation for future professional activity. Therefore, this article consistently analyzes such concepts as "professional activity", "professional education" of a mathematics teacher and their connections with the concept of methodological training of a mathematics teacher in pedagogical university.